Pemberlakuan Sifat Melawan Hukum Materil Berfungsi Negatif dalam Tindak Pidana Korupsi - Septri Yustisiani (Faculty of Law, Maranatha Christian University, 2015)
Law No. 31 of 1999 in connection with Law No. 20 of 2001 regarding Corruption Eradication has included the unlawful element, in both procedural and substantive nature, when formulating the corruption act provision. In the legal doctrine, the substantive unlawful nature is categorized, based on its function, into two categories, namely positive and negative. The negative substantive unlawful nature is important to keep the spirit in eradicating corruption to not run amok, and to give protection to the actor, which is innocent based on substantive law. However, such criminal law policy, that accommodates substantive unlawful nature, has been declared as not legally binding by the Constitutional Court in its Decision No. 003/PUU-IV/2006 as it is considered conflicting with the legal certainty, which is one of the principles in the rule of law. Therefore, this research will analyze the above decision and the continuity in applying the negative function of the substantive unlawful nature to the corruption crime, which could be seen from the court decisions; and relates it, with the purpose of law.